O homem e o espaço hospitalar : o Edifício Manoel Tabacow Hidal Hospital Albert Einstein (1958) - Melendres, Carolina Nunes (2011)
This essay discusses the concept of humanization applied in hospitals, examining its connection to the healing process and well-being, plus the link between the concept and design methods that improve architecture of hospitals and health promotion. Over time, hospital architecture has undergone various transformation supported by the evolution of medical knowledge and technology, as well as the appreciation of health and patients. The hospital went from a lifeless and absent building for an instrument to promote active assistance to medical practices and needs of its users, both physical and psychological. The shaping of this so called therapeutic places, seeks to synthesize this new hospital building dynamic that approach the figure of man and its complexities, in order to make it more receptive and personal: humanized. The careful examination of the design process and hospital production of architect Rino Levi whose thoughts are representative within the illustrated scenario reveals its close relationship with the principles of humanization in hospital architecture. Specifically, the case of Manoel Tabacow Hidal building designed by Rino Levi s team, in 1958, is deepened as the object of investigation